Kingdom vision 2030 and the women’s empowerment in Saudi Arabia : an empirical investigation - Alharbi, Mai Mohammed H (Penerbit Universiti Kebangsaan Malaysia, 2022)
Empowerment of women is the mirror of a society's civilization and development. It is vital and necessity for the success of the society’s comprehensive development. This study aims to explore the role played by the "Kingdom's vision 2030" in empowering Saudi women. The study applied a questionnaire consisting of five axes that express the awareness of empowering Saudi women according to the “Vision 2030”. A total of 152 responses were received in two months. The study used both the descriptive and analytical approaches to analyse the collected data. The results showed that there are statistically significant differences in the awareness of empowering Saudi women in the view of Vision 2030 based on the respondents ages, nature of their profession and level of education. The study recommended that more opportunity for women in terms of education and property ownership can encourage women to put more efforts towards the development of the Kingdom.